2008
DOI: 10.1108/17561370910915357
|View full text |Cite
|
Sign up to set email alerts
|

The impact of remittance income on rural households in China

Abstract: PurposeThe objective of this paper is to evaluate the impact of remittance income on rural households in China.Design/methodology/approachUsing data from a large survey of farming households in three Chinese provinces, the impacts of remittances and other types of income on consumption, production expenditures is evaluated. The econometric models used in this study include logit, tobit and ordinary least squares models.FindingsIt is found that remittances increase nondurable consumption, but not as much as loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
1
10
1
Order By: Relevance
“…The preliminary results above confirm previous empirical findings of studies on China, i.e., that both motivations are at work (Secondi, 1997;Snyder and Chern, 2008). These results encourage us to explore whether such motivations transpire also when our SWB approach is used.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The preliminary results above confirm previous empirical findings of studies on China, i.e., that both motivations are at work (Secondi, 1997;Snyder and Chern, 2008). These results encourage us to explore whether such motivations transpire also when our SWB approach is used.…”
supporting
confidence: 79%
“…More recently, studies have explored this research question in the context of China. The main result of these studies suggest that the motivation behind remittances in China is mixed, since altruism alone is not capable of explaining their remittance behaviour (e.g., Secondi, 1997;Ma, 2001;Bai and He, 2002;Murphy, 2002;Feng and Heerink, 2008;Snyder and Chern, 2008). SWB and motivations behind remittances As a preliminarily check to identify which motivation dominates in our sample, we investigate -as in the standard approach -the relationship between the income (before remittances) of the family left behind and the level of remittances.…”
mentioning
confidence: 99%
“…The effect of remittances on lowest income households in Thailand was also shown to be substantial with 85% of the poorest households reporting receiving remittances, compared with 34.2% of the wealthiest (Osaki, ). In China (Snyder and Chern, ), it was households from the middle income quartiles that were more likely to receive a remittance (40%), compared with 32% in the lowest quartile. Although Snyder and Chern () indicated that the cost of migration is a barrier for poorer households, such a conclusion is difficult to sustain as households were categorised according to whether they received a remittance not whether the household participated in migration.…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…In China (Snyder and Chern, ), it was households from the middle income quartiles that were more likely to receive a remittance (40%), compared with 32% in the lowest quartile. Although Snyder and Chern () indicated that the cost of migration is a barrier for poorer households, such a conclusion is difficult to sustain as households were categorised according to whether they received a remittance not whether the household participated in migration. We would like to add an important caveat; when income was further disaggregated by Snyder and Chern () into the lowest and highest decile, 25% of households in the lowest 10% reported receiving a remittance.…”
Section: Overview Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation